2014
DOI: 10.1016/j.solener.2013.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Model predictive control of a solar-thermal reactor

Abstract: DateThe final copy of this thesis has been examined by the signatories, and we find that both the content and the form meet acceptable presentation standards of scholarly work in the above mentioned discipline.iii can preserve product quality and maintain stable product compositions, resulting in a more efficient and cost-effective operation, which can ultimately lead to scale-up and commercialization of solar thermochemical technologies. ABSTRACTIn this work, we propose a model predictive control (MPC) system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 49 publications
(149 reference statements)
0
13
0
Order By: Relevance
“…The conduction term then simplifies as shown in Eq. (12). In a similar manner, the convection term simplifies as shown in Eq.…”
Section: Heat Transfer Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…The conduction term then simplifies as shown in Eq. (12). In a similar manner, the convection term simplifies as shown in Eq.…”
Section: Heat Transfer Analysismentioning
confidence: 88%
“…However, since these reactors have fixed apertures, they are not able to compensate for large fluctuations in the irradiance without sacrificing other aspects of the process. The most commonly used approach to maintaining semi-constant temperatures within the solar reactor is adjusting the feedstock's flow rate to compensate for any irradiance fluctuations [11,12]. However, this approach disturbs the flow dynamics and is usually not feasible in processes where the flow pattern has to be preserved.…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuations in solar radiation lead to a time-varying process heat input to the receiver which disturb the temperature stability and decrease the efficiency of the process. Closed loop control can cope with these instabilities and keep the temperature constant and increase the efficiency of the system [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study, Sadde et al used a model predictive controller for temperature regulation of a carbon steam gasification reactor. Their simulation results indicated that the controller can efficiently reject the disturbances in solar irradiation via the manipulation of the flow rates into the reactor [7]. Solar power entry manipulation is another approach which had been used for temperature control in solar reactors.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Saade et al employed unsteady mass and energy balances to develop a simplified dynamic model for a solar thermal transport tube reactor [9]. As a follow up study, they developed a Model Predictive Control (MPC) strategy to regulate the solar reactor housing carbon steam gasification process [10]. Recently, Li et al presented a transient 3D model for hydrogen and carbon monoxide production in a solar reactor by coupling Monte Carlo ray tracing and Lattice Boltzmann (LB) model [11].…”
Section: Introductionmentioning
confidence: 99%